Gulabi Gang - Jain, Nishtha (India : Grude, Torstein, 2012)
Bundelkhand in central India is a place of desolation, dust, and despair; notorious for its rebels-turned-armed bandits. However, it is witnessing a new kind of rebellion with an unusual cast of characters. The pink sari-clad women of the Gulabi Gang use words as weapons demanding their rights, submitting petitions and haranguing corrupt officials. Armed with lathis (cudgels), they go to villages where particularly egregious mistreatment of women has taken place. Unafraid to confront husbands, fathers, brothers, village elders, and undeterred by sneering policemen and condescending bureaucrats, they demand investigations and justice. Men ridicule them at their own peril. Led by the energetic and charismatic Sampat Pal, they have to face resistance, apathy and corruption. Sometimes entire villages connive against them to protect the perpetrators of violence. The film pulls us into the center of these blazing conflicts and uncovers a complex story, disturbing yet heartening.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films